The Los Angeles Lakers encyclopedia - Shmelter, Richard J., 1959- (McFarland & Company, Inc., Publishers, 2012)
"This definitive encyclopedia of the Lakers provides all vital data pertaining to each season of the team's first 50 years in Los Angeles, including biographies of Hall of Famers, other great performers, and coaches; complete rosters; season-by-season schedules and statistics; draft picks; and records and individual accomplishments"--Provided by publisher